Who goes there? [personal identity systems].
Just a few years ago, getting to work involved a nod to someone in the building lobby or a wave to an office receptionist. Today, those friendly greetings have been replaced in many offices by smart cards. Soon the use of smart cards at these sites is expected to make way for biometric identifiers: handprints, fingerprints, eye scans, or face-recognition signatures. On the way to work, too, one's face or car may be scanned or photographed at traffic signals, bank machines, shopping malls, parks, and sidewalks. As methods of identification, however, biometric technologies are still immature and are still capable of being defeated.
Keywords: Biometric identifiers; Eye scan identifiers; Face-recognition signatures; Fingerprint identifiers; Handprint identifiers; Personal identity systems